An Analysis of the Application of the Harmony Search Algorithm to Solving the Nurse Rostering Problem. - Lartey, Kelvin; Akowuah, Emmanuel Kofi (CIN: Computers, Informatics, Nursing)
The nurse rostering problem describes the task of distributing nurses over working time slots, called shifts, in such a way that the workforce demand for each shift in a scheduling period is met, while ensuring that each nurse is not overttasked or undertasked. This problem is a major issue in Ghana, which this research aims to tackle. To that end, the performance of a heuristic algorithm that showed promise, called the Harmony Search algorithm, is examined. The algorithm, as applied to solving the nurse rostering problem in a hospital in Ghana, was implemented and evaluated with the Python programming language. The results suggest that the algorithm performs well in generating 1-week duty rosters but falters for extended periods, indicating that it may not on its own be potent enough to handle optimization problems. Finally, we outline some recommendations future researchers may want to note.